Kedudukan Anak Astra (Anak Luar Kawin) dalam Hukum Keluarga dan Kewarisan Adat Bali - I Gede Yudha Rana; I Made Suwitra; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
The presence of a child in the family is happiness as a manifestation of the fruit of a husband and wife's love. Having children is everyone's dream, especially when starting a new family or legal marriage. However, this is inversely proportional to children who are born without a previous legal marriage relationship so that the child is included in the class of children outside marriage or Astra children in accordance with Article 43 of Law Number 1 of 1974 concerning Marriage. This child out of wedlock sometimes becomes a problem in the family because not all stepfathers accept their existence. This study aims to reveal the position of children in traditional inheritance families in the Malet Village of Kutamesir and analyze the protection of Astra children in family law and inheritance in the Indigenous Village of Malet Kutamesir. This study uses an empirical legal research type with a conceptual approach. The data used are primary and secondary data obtained through interview techniques and literature study techniques and analyzed qualitatively and legal interpretation with a descriptive final presentation. The results of this study reveal that an astra child only has a legal position in inheriting his mother's property and an astra child has the right to get protection from whatever happens around his life, be it at home or outside the home.